PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA HYPERMART PURI INDAH JAKARTA BARAT - Alfin Rizki Fauzan; Paeno Paeno (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the effect of work discipline and physical work environment on employee performance at Hypermart Puri Indah, West Jakarta, both partially and simultaneously. The research employed a quantitative method with an associative approach, collecting data through questionnaires distributed to 92 employees of Hypermart Puri Indah. The data were analyzed using multiple linear regression with the assistance of SPSS version 27. The results show that partially, work discipline (X1) has a positive and significant effect on employee performance (Y), as indicated by the t-value > t-tabel (12.724 > 1.987) and significance level of 0.00 < 0.05. Similarly, the physical work environment (X2) positively and significantly affects employee performance with a t-value > t-tabel (11.710 > 1.987) and a significance level of 0.00 < 0.05. Simultaneously, work discipline and physical work environment have a significant effect on employee performance with an F-value > F-tabel (110.475 > 3.099) and a significance level of 0.00 < 0.05. The coefficient of determination (R²) of 65.4% indicates that both variables jointly influence employee performance, while the remaining 34.6% is affected by other factors outside this study. These findings emphasize the importance of maintaining consistent work discipline and creating a conducive physical work environment to enhance employee productivity and performance. Therefore, the company is encouraged to strengthen its disciplinary system and improve workplace conditions to achieve optimal performance outcomes.